2002
DOI: 10.1103/physreve.66.056204
|View full text |Cite
|
Sign up to set email alerts
|

Bubble and spherical air shell formation dynamics

Abstract: We studied the formation dynamics of air bubbles emitted from a nozzle submerged in aqueous glycerol solutions of different viscosities. We describe the evolution of the bubbling regimes by using the air flow rate as a control parameter and the time between successive bubbles as a dynamical variable. Some results concerning bubbling coalescence were emulated with a combination of simple maps. We also observed the formation of air shells surrounding liquid drops inside the liquid, known as antibubbles. The anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 8 publications
4
26
0
Order By: Relevance
“…The same phenomena in airaqueous glycerol solution were reported by Tufaile and Sartorelli. 27 In their experiments, tiny bubbles, known as antibubbles, were produced after the coalescence of two bubbles in the period-2 bubbling regime at high gas flow rates. An antibubble is a shell of air surrounding a drop of liquid inside the liquid.…”
Section: Regimes Of Low Intermediate and High Weber Numbers (Gas Flomentioning
confidence: 99%
See 1 more Smart Citation
“…The same phenomena in airaqueous glycerol solution were reported by Tufaile and Sartorelli. 27 In their experiments, tiny bubbles, known as antibubbles, were produced after the coalescence of two bubbles in the period-2 bubbling regime at high gas flow rates. An antibubble is a shell of air surrounding a drop of liquid inside the liquid.…”
Section: Regimes Of Low Intermediate and High Weber Numbers (Gas Flomentioning
confidence: 99%
“…In most of the theoretical models 17,18,22,32,33,38 developed by these workers, the effect of the previously formed bubble on the growth of the bubble at the orifice were not taken into account, although Zhang and Shoji, 21 Chuang and Goldschmidt, 39 and Deshpande et al 40 developed models by taking into account the wake effect of the previous bubble or bubble coalescence. Depending on the operating parameters (gas flow rate, orifice diameter, surface wetting characteristics, and physical properties of the liquid phase), different regimes [19][20][21]23,26,27,41 are discerned as period-1, period-2 with pairing or double coalescence (see below), period-3 (triple coalescence), period-4 (quadruple coalescence), and finally chaotic bubbling regimes. 42 Most importantly, Higuera and Medina 35 reported that the period-2 regime consists of the pairing regime 20,21,23 and the double coalescence regime.…”
Section: Introductionmentioning
confidence: 99%
“…The Plateau number describes the relative contribution of the surface tension effects versus the centrifugal effects in a rotating drop. [271][272][273][274][275][276][277][278]. In practice, a large Plateau number indicates an almost spherical drop where the rotation effects can be neglected as compared with a stronger surface tension.…”
Section: Constantin Brâncusimentioning
confidence: 99%
“…There are three reasons why the 2D drop-like systems are now so widely studied: they lead to the greatest variety of patterns and waves on the free surface, they are relatively easy to handle theoretically, and experimental procedures are readily available [271][272][273][274][275][276][277][278]. The understanding of the formation, propagation, stability, bifurcation, breakup, and clustering of waves, patterns, and shapes on compact fluid boundaries of isolated drops are of fundamental importance in fluid dynamics problems, printing and painting technologies, and design in the medical and pharmaceutical industries.…”
Section: Leidenfrost Dropsmentioning
confidence: 99%
“…They were coined "antibubbles" in the 1970s [11]. Only a few works [1][2][3][12][13][14] have been devoted to a quantitative study of antibubbles. They are mainly focussed on either the formation of antibubbles or the stability of such objects.…”
Section: Antibubblesmentioning
confidence: 99%